Design and accuracy evaluation of AI orthognathic surgery plates - LIU Zhikai; XU Chunwei; ZHU Zhaokun; LIU Yao; LUO En (Kouqiang hemian waike zazhi)
[Objective:] To establish a design program for orthognathic surgical splints based on artificial intelligence (AI), and to compare the precision between the AI splints and manual digital splints. [Methods:] This research established an AI algorithm for orthognathic surgical splints and obtained the available automatic design program. The time required for designing surgical splints in the same case was compared. Besides, 40 dentition models of patients with skeletal Class Ⅱ malocclusion (20 for mandibular surgery, and 20 for bimaxillary surgery) were included for comparison. The splints were designed by AI program and manual digital software respectively and scanned for the digital data to compare the difference. [Results:] The overall deviation between the AI and manual digital splints in guiding the positioning of the models was less than 0.1 mm, indicating that there was no significant difference between them. Comparison of cusp position showed that the mean deviation distance between the AI and manual digital splints was about 0.10-0.14 mm. The application of the AI program can greatly reduce the design time in both the mandibular surgery [(10.7±2.4) s:] and the bimaxillary surgery [(21.5±3.9) s]. [Conclusion:] There is no significant difference in accuracy between AI and manual digital splints, and AI program can improve the design efficiency of orthognathic surgical splints.